CRITICAL READING SKILL IN DIFFERENT AGE LEVELS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
From different age groups and educational settings, the thesis include a wide range of viewpoints and approaches about the critical reading skill. In order to shed light on instructional practices and student views, Dogan and Tosun (2019) concentrate on the difficulties and facilitators faced while integrating critical reading into English as a Foreign Language (EFL) courses. Ferdous and Alam (2022) explore the complex idea of critical reading, offering fundamental understandings of the theoretical underpinnings of this ability. Koray and Çetinkılıç (2020) investigate how critical reading is applied, particularly in understanding scientific materials, emphasizing the influence it has on academic achievement and problem-solving skills. Ozensoy (2021) examines the relationship between academic achievement in the field of social studies and the ability to read critically, providing actual data to bolster the significance of the relationship. Suh (2019) concludes with a case study that explores the practices of critical reading among Korean university students in an EFL context. This thesis adds to our understanding by incorporating cultural factors and practical applications.